The Metaphorical Representation of Coronavirus in Iraqi Newspaper Cartoons - Tuama Jasim Al-Saedi, Hayder ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The current study aims to explore the metaphorical representation of coronavirus in newspaper cartoons. Eighty-one cartoons, illustrated by well-known cartoonists, are collected from Iraqi daily newspapers and limited to the cartoons that shed light on “coronavirus.” All the verbal and visual cues are taken in consideration in these cartoons. They were classified according to their metaphorical conceptual domains and themes. The selected cartoons are analyzed in two different ways. First, they are analyzed using Lakoff and Johnson’s (1980) Conceptual Metaphor Theory to verbalize the metaphorical concepts of the verbal and/ or visual cues in these cartoons. Then, they are analyzed using Forceville’s (1996; 2008) Pictorial Metaphor and Sobrino’s (2017) Multimodal Metaphorical conceptualization. The findings revealed that the sampled cartoons included visual/ pictorial and multimodal metaphors to deal with different socio-political and economic affairs. In conclusion, this study showed that the coronavirus pandemic was addressed in different metaphorical concepts such as WAR, GAMES, etc. and shed light on different issues in the society such as the collapse of economy, vaccine, corruption to show negative connotation due to the emergence of coronavirus in these cartoons such as corruption pandemic. The metaphorical representation of coronavirus, in WAR metaphor, shows positive connotation since it shed light on the confrontation of the pandemic and fighting it.